Skin diseases among the tribal population of Kerala: the challenges and way forward - Surendran Maheswari Simi; Regi Jose; Thekkumkara Surendran Anish (BMC, 2024)
Abstract Background Kerala has a history of achievements in health through acting on the distal social determinants, but certain communities like tribals were pushed back from the stream of social development and health achievements. Subsequently, the lifestyle and the poor living conditions of tribes make them more prone to several diseases including skin diseases. However, neither the burden nor the situation of the same in the tribal population in several parts including Kerala is seldom assessed. Main body The lack of awareness about the symptoms, complications, and management options as a part of the social backwardness has led to the concentration of certain diseases like Leprosy among the tribal community. In addition, the tribal population is under the threat of infectious diseases of public health significance like Leishmaniasis (CL). The tribal population owing to ignorance neglects the skin lesions or uses their local remedies. Tribes might have been using many local remedies for their issues, but the emerging skin diseases may not be amenable to local remedies and often impose significant public health concerns. Developing and maintaining an effectively functioning health system in these difficult-to-reach terrains is also a challenge. The pattern of skin diseases among tribals residing in environmentally sensitive localities is an indicator for the need for more social, economic and geospatial inclusion. Skin lesions of the tribal population should be kept under active surveillance activities through the integrated health information platform (IHIP) and it should follow a vigilant public health response if there are clusterings. A dedicated evidence-based system should be developed to diagnose and treat skin diseases of tribal people residing away from the availability of specialist care using local resources and community-level workers. Conclusion The rampant skin diseases among tribals are the product of their unacceptable socio-economic status and living conditions. It could only improve through interventions focusing on social determinants of health. Improvements in the living conditions of tribals are sustainable long-term solutions, but such solutions should be coupled with medium-term and short-term strategies.